MENGEMBANGKAN KEMAMPUAN MENGELOLA EMOSI ANAK MELALUI METODE BERCERITA DI TK IT BAITUSSHALIHIN ULEE KARENG - Yendri Wahimah; Musnizar Safari (STKIP An-Nur, 2021)
The children aged 5-6 years old are basically able to manage emotions naturally, but in TK IT Baitusshalihin kindergarten, especially group B2, there are still those who not able to manage emotions properly. This research to develop the ability to manage emotions in group B2 aged 5-6 years old at TK IT Baitusshalihin kindergarten Ulee Kareng. This research is a descriptive qualitative research with a classroom action reseacrh approach. The subject in this study were 11 children that consisting of 6 boys and 5 gilrs collecting data using class observation techniques and interviews with B2 class teachers. The data analysis technique uses the percentage formula for each cycle action. The results of this research method found that storytelling can improve the ability to manage childrens emotions. This can be seen from the previous ability to manage childrens emotions below 75%. Although in the first cycle there was only one child whose ability to manage emotions was above 75%, but in the second cycle there were nine children whose ability was above 75%. Keywords: Managing emotions, storytelling method, and early childhood.